2000
DOI: 10.1111/1469-8986.3720262
|View full text |Cite
|
Sign up to set email alerts
|

Basic auditory dysfunction in dyslexia as demonstrated by brain activity measurements

Abstract: Although the generality of dyslexia and its devastating effects on the individual's life are widely acknowledged, its precursors and associated neural mechanisms are poorly understood. One of the two major competing views maintains that dyslexia is based primarily on a deficit in linguistic processing, whereas the other view suggests a more general processing deficit, one involving the perception of temporal information. Here we present evidence in favor of the latter view by showing that the neural discrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(66 citation statements)
references
References 14 publications
5
59
1
1
Order By: Relevance
“…In a previous study in our laboratory, we found that developmentally dyslexic children were somewhat impaired in temporal acuity tasks in all sensory modalities investigated, relative to their agematched controls (Laasonen et al, 2000). Other Finnish studies (Hari & Kiesilä, 1996;Hari et al, 2001;Hari, Valta, & Uutela, 1999;Helenius, Uutela, & Hari, 1999;Kujala et al, 2000) have found impaired processing of rapid auditory and visual sequences in adult dyslexics, but these studies did not include multiple modality comparisons.…”
mentioning
confidence: 61%
“…In a previous study in our laboratory, we found that developmentally dyslexic children were somewhat impaired in temporal acuity tasks in all sensory modalities investigated, relative to their agematched controls (Laasonen et al, 2000). Other Finnish studies (Hari & Kiesilä, 1996;Hari et al, 2001;Hari, Valta, & Uutela, 1999;Helenius, Uutela, & Hari, 1999;Kujala et al, 2000) have found impaired processing of rapid auditory and visual sequences in adult dyslexics, but these studies did not include multiple modality comparisons.…”
mentioning
confidence: 61%
“…The authors interpreted their findings as a speech-specific deficit, however they did not exclude the possibility of a more general deficit in auditory processing. Indeed, deficient pitch (Baldeweg et al, 1999;Kujala et al, 2006) and temporal discrimination (Kujala et al, 2000(Kujala et al, , 2003 have also been reported in dyslexia (for a recent review on theories of dyslexia, including a general acoustic processing deficit account, see Schulte-Körne and Bruder, 2010). Recent results from a multi-feature paradigm in 6 year old children (Lovio et al, 2010) suggest wide-spread auditory deficits in children at risk for dyslexia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies employing stop consonant-vowel syllables report an attenuated mismatch response in learning-disabled or dyslexic children compared to typically developing controls (Kraus et al, 1996;Schulte-Körne et al, 1998;Bradlow et al, 1999). Likewise, in adults with a history of dyslexia, Kujala et al (2000) observed atypical MMR patterns to auditory temporal information that were paralleled by poorer behavioural discrimination performance.…”
Section: Electrophysiological Studiesmentioning
confidence: 98%